The house of the scorpion - Farmer, Nancy, 1941- (New York : Simon Pulse, 2004)
In a future where humans despise clones, Matt enjoys special status as the young clone of El Patrn̤, the 142- year-old leader of a corrupt drug empire nestled between Mexico and the United States.
"A Richard Jackson book".
660
Newbery Medal Honor Book 2003. National Book Award Finalist. A YALSA 2003 book. Maine Student Book award list 2003-2004
Keywords: Human cloning -- Fiction; Science fiction; Cloning -- Fiction; Young adult fiction